SIGNIFICANCE OF M1 AND M2 POLARIZATION OF MONOCYTES-MACROPHAGES IN THE BLOOD FOR ATHEROSCLEROSIS RISK ASSESSMENT IN TYPE 2 DIABETES COMPARING WITH CORONARY HEART DISEASE - К. О. Galstyan; L. V. Nedosugova; N. G. Nikiforov; К. I. Kolmychkova; Т. V. Kirichenko; I. A. Sobenin (Российский кардиологический журнал)
Aim. To assess the phenotypes of proinflammatory (M1) and anti-inflammatory (M2) activation of blood monocytes in type 2 diabetes (DM2) comparing to coronary heart disease patients (CHD).Material and methods. Totally, 55 CHD patients assessed, of those 28 (11M/17F) were first time diagnosed with DM2 at current hospitalization (HbA1c level 9,7% SD=2,4), not taking previously any glucose lowering therapy; and 27 patients with CHD (20M, 7F), with no glucose metabolism disorders. By immune enzyme assay method (IEA) proinflammatory monocyte activation was evaluated by spontaneous and interferon gamma (IFN-ɣ) induced secretion of proinflammatory cytokine tumour necrosis factor alpha (TNF-α), and anti-inflammatory activation of monocytes by spontaneous and interleukin-4 (IL-4) induced secretion of anti-inflammatory cytokine CCL18.Results. There was found an increased ability of monocytes in DM2 patients to secrete proand anti-inflammatory cytokines comparing to the controls and CHD patients. Basal TNF-α secretion was higher than control level 2,8 times, and stimulated — 2,2 times. Values of the basal and stimulated TNF-α secretion in CHD patients were significantly lower than in controls. There was positive correlation of HbA1c level and basal secretion of TNF-α. Basal and stimulated secretion of anti-inflammatory cytokine CCL18 in DM2 patients was significantly higher than control level — 28 pg/mL (SD=3) and 1158 (SD=68) pg/mL of the cultural medium, respectively, and in CHD patients these parameters were lower than the control level — 0,26 pg/mL (SD=0,14) and 65 (SD=33) pg/mL, respectively. Conclusion. In DM2 there is disbalance of M1/M2 activation of monocytes comparing to controls and CHD, that points on overactivation by proinflammatory phenotype.